Essential maps for the lost - Caletti, Deb (Simon Pulse, 2016)
"When Mads discovers a dead body while she's swimming in the lake, she begins to obsess over who the woman was and what led her to commit suicide by jumping off a bridge. But when she starts to fall for Billy, the woman's troubled son, Mads isn't sure how much longer she can keep her obsession a secret"--